2022
DOI: 10.1002/ael2.20083
|View full text |Cite
|
Sign up to set email alerts
|

Mercury accumulation in honey bees trends upward with urbanization in the USA

Abstract: Urbanization has profound implications for associated ecosystems and organisms. Monitoring pollutants inform risk assessments for human and wildlife health. Honey bees (Apis mellifera) forage widely and collect food from many sources. Thus, they may be a robust integrator of environmental pollutants. Here, we collected honey bees from 10 different locations across the United States to quantify their content of total mercury (THg) and methylmercury (MeHg). Although our limited sample size prevented a meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Similar to other chemical exposures, a multitude of intrinsic and extrinsic factors influence the exposure and impact of these pollutants on honey bees. The abundance of pollutants positively increases the risk of exposure, for example, heavy metal pollution of the environment has increased with the urbanization of geographical areas and the same trend has been observed in the accumulation of Pb in honey bees [64]. However, the uptake of different toxic elements by honey bees can vary even within the same hive [11].…”
Section: Potentially Toxic Elementsmentioning
confidence: 97%
“…Similar to other chemical exposures, a multitude of intrinsic and extrinsic factors influence the exposure and impact of these pollutants on honey bees. The abundance of pollutants positively increases the risk of exposure, for example, heavy metal pollution of the environment has increased with the urbanization of geographical areas and the same trend has been observed in the accumulation of Pb in honey bees [64]. However, the uptake of different toxic elements by honey bees can vary even within the same hive [11].…”
Section: Potentially Toxic Elementsmentioning
confidence: 97%
“…They found that rice from these farms poses low risk for consumers and note the importance of testing under different soil conditions. A preliminary study by Waiker et al. (2022) shows a connection between urbanization and mercury levels in honey bees. The authors suggest that these pollinators may be useful biomonitors of mercury pollution.…”
mentioning
confidence: 96%